Culture and personality: R. Wagner "Between music and life" - I. V. Zhyvohliadova (Ukrainian Cultural Studies, 2021)
Modern trends in the development of culture, its artistic component, have actualized the issues of in-depth study of the world and national heritage. The article analyzes the creation of an outstanding personality – R. Wagner (1813 – 1883), with its inherent contradiction, complexity, versatility, as a representation of the creative potential of a person’s participation in the processes of cultural creation. An integrative, culturological analysis of the specifics of his composing activity as a cultural phenomenon makes it possible to highlight the role of an artist, thinker, reformer in the space of functioning of a certain cultural, in this case romantic, tradition, to explore the subjective experience of transforming art into a cultural practice of improving society. Through the works of a German composer, the anthropo-creative potential of interaction between culture and personality is analyzed. Concentrating all the trends and crises of romanticism in the music of the second half of the XIX century, the work of the composer as a reformer demonstrates current creations of the relentless desire to transform the world around, which encourage artists to different creative reactions to the collision of modern life, which, in turn, involves others in understanding its essence.